Analisis Dampak Operaional PLTU Jeranjang Terhadap Kondisi Sosial dan Ekonomi Masyarakat Di Kabupaten Lombok Barat - Rancak, Gendewa Tunas; Azmiyati, Uzlifatul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
PLTU Jeranjang, West Lombok Regency, is a power plant that uses low-calorie coal. The activities and all power generation activities, including the PLTU Jeranjang, have the potential to have an impact on the social and economic conditions of the community around the power plant location. More in-depth research is needed regarding the impact on social and economic conditions, especially in the Jeranjang area. The aims of this research are (1) to find out how big the social and economic impact of the operational activities of PLTU Jeranjang on the community around the area of PLTU Jeranjang. (2) As a reflection and reference in efforts to increase the national electrification ratio with its impact on environmental, social, economic, and cultural conditions. The method used is a qualitative method by applying questionnaires, interviews and field observations to collect data. While the research sample used purposive sampling by considering the selection of respondents, ease of access, cost and time of the study. This study resulted that the community experienced a decrease in income up to 79%, especially fishermen and farmers. However, the level of anxiety is relatively low because %URS only reached 56%. The health impact that is often experienced by the community throughout the year is Upper Respiratory Tract Infection (ARI). The magnitude of the disturbance in fishing activities is classified as having a sufficient impact because 71% of fisherman feel a change in the typology of fishing which has an impact on the economy. The amount of disturbance to fishing activities is quite adequate with an FAI value of 0.003391. The operational activities of the PLTU Jeranjang as a whole have an impact that is still included in the low category so that this impact can be minimized by optimizing the monitoring, control, treatment, and information disclosure between the PLTU Jeranjang and the community.